Model Penugasan Belajar di Rumah Yang Menyenangkan Bagi Siswa di Masa Pandemi Covid 19 - Basuki, Slamet (JURNAL PENDIDIKAN DASAR NUSANTARA, 2020)
A FUN HOME STUDY ASSIGNMENT MODEL FOR STUDENTS DURING THE COVID 19 PANDEMIC Abstract: This Fun Learning Home Assignment Model Article for Students in the Covid Pandemic Period 19 is an article that contains ideas derived from the author's experience in distance learning during the covid pandemic 19. The purpose of this article is; 1. Provide teachers with creative ideas (ideas) about learning assignments at home that are fun for students in the Covid 19 pandemic; 2. Explain a fun assignment model for students in the covid pandemic 19; 3. The teacher can carry out creative and fun learning in the emergency of the Covid 19 pandemic; 4. Teachers can carry out creative and fun assignments during the Covid 19 pandemic emergency; 5. As a literacy study in preparedness to deal with the Covid 19 pandemic outbreak; The method in the article on the assignment model of learning at home that is fun for students in the pandemic covid 19 period is an explanation of the assignment of learning at home that is fun with a few points outlined in detail. Keywords: assignment model, learning fun, covid pandemic 19